Interdisciplinarity in the Scholarly Life Cycle Learning by Example in Humanities and Social Science Research - Bijsterveld, Karin; Swinnen, Aagje (Springer Nature, 2023)
This open access book illustrates how interdisciplinary research develops over the lifetime of a scholar: not in a single project, but as an attitude that trickles down, or spirals up, into research. This book presents how interdisciplinary work has inspired shifts in how the contributors read, value concepts, critically combine methods, cope with knowledge hierarchies, write in style, and collaborate. Drawing on extensive examples from the humanities and social sciences, the editors and chapter authors show how they started, tried to open up, dealt with inconsistencies, had to adapt, and ultimately learned and grew as researchers. The book offers valuable insights into the conditions and complexities present for interdisciplinary research to be successful in an academic setting. This is an open access book.